Clinical and genetic characteristics in a central-southern Chinese cohort of early-onset Alzheimer's disease - Liang, Zhihou; Wu, Yan; Li, Chuanzhou; Liu, Zhijun (Frontiers in Neurology, 2023)
Mutations in the presenilin 1 (PSEN1), presenilin 2 (PSEN2), and amyloid precursor protein (APP) genes have been commonly identified in early-onset Alzheimer's disease (EOAD). Some of mutations in the three causative genes, especially the PSEN1 gene, result in variable phenotypes and exhibit clinical heterogeneity among EOAD families. Using next-generation sequencing (NGS), we performed a genetic screening in a Chinese cohort of 18 EOAD patients, consisting of 5 familial EOAD and 13 sporadic cases. We identified two likely pathogenic PSEN1 mutations (one novel) and a novel APP mutation in 3 cases of EOAD, 2 familial and 1 sporadic, respectively. Additionally, we detected a few variants of uncertain significance (VUS) in several genes, including not only the two known variants in PSEN2 (p.H169N and p.V214L), but also genes causal for other types of dementia or previously identified as risk factors for AD, suggesting the possible involvement of multiple genes in the etiopathology of AD. The patients carrying PSEN1 mutations had an earlier mean age at onset than those with PSEN2 or APP variants. The initial symptoms varied greatly among patients in the EOAD cohort from progressive memory impairment and epilepsy to uncommon motor symptoms, like involuntary tremor in the upper extremities. In conclusion, our study provides further evidence of the genetic profile of EOAD patients from China and expand the mutation spectrum of both PSEN1 and APP. In addition, our results highlight the clinical heterogeneity in patients with EOAD and mutations in PSEN1, PSEN2 and APP, and suggest that strong effects of genetic variants on clinical phenotypes. Future functional studies are needed to clarify the interaction between AD-causative gene mutations and phenotypic heterogeneity.